2014
DOI: 10.1155/2014/347810
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Resection for Rectal Cancer: What Is the Evidence?

Abstract: Laparoscopic colectomy for colon cancer is a well-established procedure supported by several well-conducted large-scale randomised controlled trials. Patients could now be conferred the benefits of the minimally invasive approach while retaining comparable oncologic outcomes to the open approach. However, the benefits of laparoscopic proctectomy for rectal cancer remained controversial. While the laparoscopic approach is more technically demanding, results from randomised controlled trials regarding long term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…In line with previous review and mate-analysis, [ 6 , 19 ] there was no difference in lymph node harvested. We explained it that both HALS and OS need follow the principles of oncologic surgery.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In line with previous review and mate-analysis, [ 6 , 19 ] there was no difference in lymph node harvested. We explained it that both HALS and OS need follow the principles of oncologic surgery.…”
Section: Discussionsupporting
confidence: 89%
“…[ 39 41 ] In our meta-analysis including 15 studies with 1962 patients, HALS group revealed a significantly less blood loss and smaller incision length, which are in line with the previous meta-analysis and reviews. [ 6 , 16 , 19 ] This demonstrated that HALS can improve cosmesis for patients compared with OS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Currently, surgery remain the best treatment for colorectal cancer, which includes conventional laparoscopic surgery, hand-assisted laparoscopic surgery, robotic surgery, single-pore laparoscopic surgery, and open surgery. [3,4]…”
Section: Introductionmentioning
confidence: 99%
“…Rectum cancer has been observed as the fourth frequent cancer among men and the second frequent cancer among women in our country [2]. Currently, the first step treatment in rectal cancer is surgery [3]. Rectal cancer surgery has advanced significantly in the recent years.…”
Section: Introductionmentioning
confidence: 99%